HIGH QUALIFIED: A NEW METHOD TO PREVENT HOSPITALIZATION - Héllen Melo Pereira de Britto, Meire; Ferrarezi do Sim, Samara (Health and Society, 2022)
Introduction: With the increase in life expectancy in Brazil (with an older population), the number of accidents, chronic and degenerative diseases, required the current health system to develop and offer assistance focused on holistic care. Responsible discharge is a process in which users leave a point in the health care network, in this case the hospital, and are received in primary care. Objective: Conceptualize highly qualified. Methodology: An integrative research methodology was used, in which articles were searched in online databases, in order to demonstrate the impact on care and knowledge on the topic addressed. Results: The high level of communication between the multiprofessional team and between the intra- and extra-hospital environment are the biggest obstacles to the realization of qualified discharge.